Factors Influencing Organizational Performance with Organizational Citizenship Behavior as Mediating Variable - Raffles Juni Aswin H; Marjoni Rachman; Ivana Nina Esterlin Barus (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Organizational effectiveness depends on employee attitudes and behavior. This study aims to examine the influence of transformational leadership, job satisfaction, and organizational commitment on organizational performance and to investigate the mediating effect of organizational citizenship behavior in these relationships. Using a quantitative approach, data from 67 civil servants at the Class I TPI Samarinda Immigration Office were analyzed using Partial Least Squares Structural Equation Modeling to assess direct and indirect relationships among key variables. The results indicate that transformational leadership and job satisfaction have a significant direct effect on organizational performance, whereas organizational commitment does not demonstrate a direct influence. Instead, job satisfaction and organizational commitment affect performance indirectly through organizational citizenship behavior. The findings show that transformational leadership and job satisfaction have a direct, significant effect on organizational performance, whereas organizational commitment does not. Job satisfaction and organizational commitment significantly promote OCB, but transformational leadership does not. OCB itself is a significant determinant of organizational performance and effectively mediates the relationships of job satisfaction and organizational commitment with performance, but not the relationship involving transformational leadership. These results emphasize the importance of enhancing employees’ job satisfaction and organizational commitment to foster discretionary behaviors that improve organizational performance.